Vacant Lots in Downtown Fresno - Watkins, Howard::::::::: (1986)
Vacant lot at southwest corner of P and Tulare Streets; Yturri Hotel and Civic Center Square N Street offices in background Site of future Robert Coyle Federal Courthouse